EXPLORING STUDENTS’ SKILL IN WRITING DESCRIPTIVE TEXT - Yahya, Anisa Mujahidah; Noni, Nurdin; Korompot, Chairil Anwar (Universitas Negeri Makassar, 2025)
This study focuses on students’ skills in writing descriptive text and factors influencing students’ skills in writing descriptive text for year 11 students at MA Sehati Maros. The research questions are: What is the level of students' skills in writing descriptive texts; and What are the factors influencing students' skills in writing descriptive texts? The objective of this research was to find out the extent of students' skills for writing descriptive texts and to find out the factors that influence the students’ skills for writing descriptive texts. The researcher used quantitative research, especially descriptive methods and a questionnaire in the research design. The population of the study was year eleven students at Madrasah Aliyah Sehati Maros. The data from descriptive methods and the questionnaire were collected and analyzed with a rubric and a Likert scale. Findings and Discussions, the research concluded that the level of students’ skills in writing descriptive text is beginner, and the factors influencing students’ skills in writing descriptive text are interest score was 71, talent 70, school 70, family 69, environment 66, and motivation 52. It means from the five factors; interest is a factor that influence students’ skill in writing descriptive text.